PROBLEMATIKA SISTEM EKONOMI ISLAM DI INDONESIA - Naelul Azmi (Prodi Hukum Ekonomi Syariah (Muamalah), 2020)
Islam provided a very wide space for the development of the economy. One of the basic principles in Islamic economics is the bermuamalah sistem . Namely that all the legal changes, unless there is an argument that forbids it, become the main driver of economic innovation that accelerates the growth of Islamic economics. However, many problems occur in the economic sistem in Indonesia, including the sistem of socialization, marketing, human resources that are less competent, Products produced from Islamic economics, Sharia Banks Turns Not Yet Sharia and the lack of attention of the Indonesian government in responding to the concept of Islamic Economics in Indonesia. This paper aims to find several solutions in socio-economic problems. It focuses on the concept of Islamic economics. The purpose of this study is to determine what obstacles are faced in the implementation of the Islamic economic sistem in Indonesia, how problems that arise and can be overcome so that they can be significantly solved. The method used in this research is library research with descriptive-analytic approach. With the results of the study show that the solutions in dealing with Islamic economic problems in Indonesia include Correlation of Educational Institutions in the Development of Sharia Banking, Attention from the Government, Show the Real Role of Sharia Economy, Implementation of Dinar and Dirham Currency, Office Network, Implementation of Firm and Sistematic Regulation, Improving the Quality of Human Resources that are Less Competent and Professional, Training / Education / Socialization to Employees and the Community, Innovative Marketing, Product Innovation, Reorientation to the Real Sector and Improving Services and Professionalism.